LISTERIA MONOCYTOGENES RISK EVALUATION IN READY TO EAT DELI PRODUCTS - T Civera; V Pistone; F. Chiesa; M.A. Grassi (Italian Journal of Food Safety, 2013)
Listeria monocytogenes has become one of the major concerns for food safety. Its ability to survive and replicate at low temperature, pH and high salt concentration, makes the bacterium a threat, mostly for RTE products. For these reasons, the present research was aimed at detecting the ability of growth of L. monocytogenes in RTE products retrieved from one deli store. Samples were analysed for L. monocytogenes detection, then inoculated with the pathogen (105cell/ml) and stored at refrigeration temperature for the duration of their shelf-life (15-60 days). In all the products L. monocytogenes was not detected before experimental contamination. The challenge test evidenced that experimentally inoculated L. monocytogenes was not able to multiply for the duration of the entire shelf-life. These results indicated that the tested products could be considered as foods which are not able to support the growth of L. monocytogenes, as indicated by E.C. Regulation 2073/05. However, in order to guarantee consumer’s safety, it needs to be emphasized the need of a correct application of the GMPs, required for lowering the risk of initial contamination.